KEPASTIAN HUKUM PENGGUGAT MEMPEROLEH GANTI KERUGIAN DALAM PELAKSANAAN PUTUSAN PENGADILAN NEGERI JAKARTA BARAT No. 936/Pdt.G/2022/PN.Jkt.Brt - Samosir, Joseph Donatur; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
A lawsuit is a legal recourse regulated by the legislation in Indonesia to ensure and protect parties who have suffered harm due to the actions of others, whether as a result of contractual relationships or wrongful acts. When filing a lawsuit, the party feeling aggrieved often succeeds in proving before the panel of judges that their lawsuit meets the criteria for approval. However, issues arise when the Plaintiff cannot obtain their rights after a court decision in their favor. This is because the Plaintiff has never applied for the attachment of security against the movable or immovable property owned by the Defendant, leading to a lack of legal certainty that could protect the Plaintiff in obtaining compensation after a court decision. this research aims to determine the efforts that the Plaintiff can undertake to obtain legal certainty in securing their rights after winning a court case. In conducting this research, the author uses a research method that applies a descriptive approach to outline the legal steps taken by the Plaintiff in achieving legal certainty if the execution attachment process cannot be carried out. This research is based on data collected from secondary sources, including legislation, legal expert doctrines from books written by legal experts, and journals accessed through the internet. The conclusions drawn are based on a deductive method of conclusion drawing.